INFLUENCE OF VOCABULARY MASTERY ON READING COMPREHENSION SKILLS FOR NON ENGLISH MAJOR UNIVERSITY STUDENTS IN BATAM - Rudianto, Gaguk; Mubarak, Zia Hisni (JEE (Journal of English Education), 2018)
The purpose of this research is to reveal how significant vocabulary mastery to reading comprehension skill for non English Department of EFL Students in Batam island. Method of collecting data used in this research is series of test. They are pre-test and post test. The population of this research is about4 departments from non English major. They are about 220 samples.Method of sampling by using Taro Yamane formula. There series of test which will be applied such as Paired T- Test and Significance Test. The instrument of the reseach is pre test passage with consist of 20 questions, they are comprehension test and 10 vocabulary test and post test passage with the equal level of difficult and also consist of 10 reading comprehension questions and 10 vocabulary questions.